Multi-mechanism energy storage positive electrode and application thereof in all-solid-state battery
By adopting a multi-mechanical energy storage positive electrode in lithium-ion batteries, combining oxygen, sulfur-based positive electrode and sulfide solid electrolyte, the problems of increasing the energy density of the positive electrode material of lithium-ion batteries and irreversible decomposition of sulfide electrolytes are solved, and high energy density is achieved and reversible transformation, meeting the needs of long-term energy storage.
Patent Information
- Application Number
- CN202411002201.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-07-25
- Publication Date
- 2024-12-27
AI Technical Summary
The energy density of the cathode material of lithium-ion batteries is difficult to increase, and the oxide cathode uses precious metal elements, which is costly; the electronic conductivity of the converter sulfur-based cathode is low, the addition of conductive carbon limits the increase in energy density, and the sulfide solid electrolyte is irreversibly decomposed. Impact battery performance.
Using multi-mechanism energy storage positive electrode, combined with oxygen-based positive electrode active substances, sulfur-based positive electrode active substances and sulfide solid electrolytes, is prepared through high-energy ball milling and heat treatment, reduce the ratio of conductive carbon and electrochemically non-electrochemically active electrolytes, improve the energy density, and pass Transition metal elements catalyze the reversible conversion of sulfur-based positive electrodes and sulfide solid electrolytes.
It significantly improves the energy density of the battery, reduces the ratio of conductive carbon and electrochemically non-electrochemically active electrolytes, improves electrochemical performance, realizes the reversible transformation of sulfide solid electrolytes, and meets the needs of long-term energy storage.
Smart Images

Figure CN119208509A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the field of lithium batteries, and in particular relates to a multi-mechanism energy storage positive electrode and its application in an all-solid-state battery. Background Art
[0002] Lithium-ion batteries have made breakthroughs in body manufacturing, battery grouping and system integration, and have great advantages in terms of energy storage technology maturity, advancement and economic cost. They are currently recognized as the energy storage solution with the greatest development potential. However, the key factors restricting their large-scale and rapid development are still cost and safety issues, and there is an urgent need to develop new electrochemical energy storage lithium-ion batteries.
[0003] At present, the most commonly used positive electrodes for lithium-ion batteries include embedded-extracted oxide positive electrodes and converted sulfur-based positive electrodes, among which oxide positive electrodes include lithium iron phosphate (LiFePO4), lithium cobalt oxide (LiCoO2), lithium nickel cobalt manganese oxide (LiNi x Co y Mn 1-x- y O2), etc. The advantages of oxide positive electrodes are relatively stable structure and good cycle performance, but the current capacity of oxide positive electrodes (such as lithium iron phosphate (LiFePO4) and lithium cobalt oxide (LiCoO2) commonly used in lithium-ion batteries) is close to the upper limit of the theoretical value, and the embedded reaction of single electrons cannot break through the energy density bottleneck of the existing system, resulting in lithium-ion batteries using oxide positive electrodes being difficult to meet the urgent needs of long-term energy storage in the future. Moreover, oxide positive electrodes generally use precious metal elements such as cobalt, nickel, and manganese, and the price of raw materials remains high, which cannot meet the needs of large-scale energy storage. For example, patent CN117558870A discloses a solid positive electrode, including a positive electrode material, a solid electrolyte, and a linear conductive agent.
[0004] In contrast, there are conversion-type sulfur-based cathodes, including sulfur (S), lithium sulfide (Li2S), iron sulfide (Fe x S y ), titanium disulfide (TiS2), molybdenum disulfide (MoS2), etc. The advantages of this type of positive electrode are as follows: (1) Higher energy density: Based on the multi-electron conversion reaction, it can break through the limitations of existing lithium-ion batteries, and its capacity is often several times that of conventional oxide positive electrodes (sulfur: 1675mAh / g vs. lithium cobalt oxide: 155mAh / g); (2) Lower cost: It mainly uses non-metallic elements such as sulfur or cheap metal elements such as iron, with high crustal reserves and low raw material prices (sulfur: <4,000 yuan / ton vs. lithium cobalt oxide: ~500,000 yuan / ton).
[0005] However, after a long period of development, the energy density of conversion-type sulfur-based cathode materials has reached a bottleneck, and due to the low electronic conductivity of the conversion-type sulfur-based cathode, a large amount of conductive carbon needs to be added during the preparation of the cathode to improve its electronic conductivity, which will undoubtedly limit the further improvement of the energy density of the conversion-type sulfur-based cathode. In comparison, the oxide-type cathode has a relatively high electronic conductivity. If the oxide cathode can be introduced into the conversion-type sulfur-based cathode to replace the inactive conductive carbon, the energy density of the battery will be further improved.
[0006] The inventor's previous patent CN116666587A disclosed a composite positive electrode active material with a wide voltage range, which is a composite of a sulfur-containing positive electrode material and a lithium-containing metal oxide positive electrode material through high-energy ball milling.
[0007] CN116101989A discloses a composite positive electrode, comprising a current collector, a positive electrode layer I and a positive electrode layer II, wherein the positive electrode layer I is located on the surface of the current collector, and the positive electrode layer II is located on the surface of the positive electrode layer I; wherein the positive electrode layer I comprises a positive electrode active material, the positive electrode layer II comprises a positive electrode active material and a sulfide solid electrolyte, and the surfaces of the positive electrode active material in the positive electrode layer I and the positive electrode active material in the positive electrode layer II both have a coating layer.
[0008] CN114590850A discloses a novel sulfurized positive electrode material for a sulfide all-solid-state lithium battery, which uses a reactive gas containing the S element to react with a nickel-rich oxide positive electrode material to form a sulfurized layer on the surface of the nickel-rich oxide positive electrode material.
[0009] However, the composite positive electrode of the above patents still does not solve the problem of reversible transformation of sulfide solid electrolyte. Patent CN116666587A mainly focuses on the field of liquid batteries and does not mention its application in the field of solid-state batteries. Moreover, the patent cannot solve the decomposition problem of sulfide electrolyte in the positive electrode. In patents CN116101989A and CN114590850A, although the oxygen-based positive electrode is coated and modified accordingly, the problem of irreversible decomposition of sulfide electrolyte is also not solved. The present invention combines oxygen-based positive electrode, sulfur-based positive electrode and sulfide solid electrolyte to obtain a multi-mechanism energy storage positive electrode that can not only give full play to the capacity of the three materials, but also effectively solve the problem of reversible decomposition of sulfide solid electrolyte and realize the reversible transformation of sulfide solid electrolyte, which is expected to further improve the energy density of solid-state batteries. Summary of the invention
[0010] In order to solve the defects that the capacity of the above-mentioned lithium-ion positive electrode materials is difficult to further increase, or that increasing the capacity will lead to insufficient other electrochemical properties, the present invention provides a multi-mechanism energy storage positive electrode, which can effectively reduce the proportion of inert components such as conductive carbon and electrochemically inactive electrolytes in the positive electrode system through the joint action of oxygen-based positive electrode active materials, sulfur-based positive electrode active materials, and solid electrolytes, and has a broad research space and application prospects. The present invention provides the following technical solutions to solve the above-mentioned technical problems:
[0011] A multi-mechanism energy storage positive electrode comprises the following raw materials in parts by mass: 5-15 parts of oxygen-based positive electrode active material, 35-45 parts of sulfur-based positive electrode active material, 30-50 parts of sulfide solid electrolyte, and 3-5 parts of conductive material.
[0012] Furthermore, the multi-mechanism energy storage positive electrode includes the following raw materials in parts by mass: 5 parts of oxygen-based positive electrode active material, 40 parts of sulfur-based positive electrode active material, 50 parts of sulfide solid electrolyte, and 5 parts of conductive material.
[0013] In multi-mechanism energy storage positive electrodes, since oxygen-based positive electrode materials often contain transition metal elements such as Co, Ni, Mn, and Fe, these transition metal elements will catalyze the transformation of sulfur-based positive electrodes in multi-mechanism energy storage positive electrodes, improve the capacity and reversibility of sulfur-based positive electrodes, and make the capacity of sulfur-based positive electrodes more fully utilized. On the other hand, transition metal elements will catalyze the reversible transformation process of sulfide solid electrolytes. In a system that does not contain transition metal elements, the transformation of sulfide solid electrolytes is irreversible, and the sulfide solid electrolytes will be transformed into irreversible decomposition products. These decomposition products are chemically and electrochemically inert species. The generation of irreversible decomposition products will cause the destruction of ion and electron transmission pathways in the positive electrode, thereby causing the positive electrode material to fail to perform well.
[0014] In the traditional sulfur-based positive electrode system, since the sulfur-based positive electrode has a relatively low electronic conductivity, it is necessary to add a very high proportion of conductive carbon material to the sulfur-based positive electrode system to realize the transmission of electrons in the sulfur-based positive electrode material. However, in the multi-mechanism energy storage positive electrode material, since the oxygen-based positive electrode material often has a higher electronic conductivity, we can reduce the proportion of conductive carbon content in the traditional sulfur-based positive electrode material and replace the conductive carbon material with an oxygen-based positive electrode material with a higher electronic conductivity. The conductive carbon material is an inert material and does not contribute to the capacity of the battery. In the multi-mechanism energy storage positive electrode material, we replace part of the conductive carbon with an electrochemically active oxygen-based positive electrode material. This part of the oxygen-based positive electrode material can not only realize the original role of the conductive carbon in transmitting electrons, but also exert a certain electrochemical capacity, which will further achieve an increase in the battery capacity.
[0015] The oxygen-based positive electrode active material includes layered oxide positive electrode materials, spinel-type positive electrode materials and olivine-type positive electrode materials.
[0016] Preferably, the oxygen-based positive electrode active material includes lithium cobalt oxide (LiCoO2), lithium nickel oxide (LiNiO2), nickel cobalt manganese ternary material (LiNi x Co y Mn 1-x-y O2), lithium nickel cobalt aluminum oxide (LiNi 0.8 Co 0.15 Al 0.05 O2), lithium-rich manganese-based (xLi2MnO3·(1-x)LiMO2), lithium manganese oxide (LiMn2O4), lithium nickel manganese oxide (LiNi 0.5 Mn 1.5 O4), lithium iron phosphate (LiFePO4), lithium manganese phosphate (LiMnPO4), lithium vanadium phosphate (Li3V2(PO4)3), lithium vanadium phosphate (LiVOPO4), lithium cobalt phosphate (LiCoPO4), lithium nickel phosphate (LiNiPO4), lithium iron silicate (Li2FeSiO4), lithium ferrous fluorosulfate (LiFeSO4F), lithium iron borate (LiFeBO3), and lithium iron titanate (Li2FeTiO4).
[0017] The sulfur-based positive electrode active material is a conversion-type sulfur-based positive electrode material, including sulfur-based materials with electrochemical reversible capacity such as sulfur and metal sulfide.
[0018] Preferably, the sulfur-based positive electrode active material includes sulfur (S), lithium sulfide (Li2S), iron sulfide (Fe x S y ), titanium disulfide (TiS2), molybdenum disulfide (MoS2), etc.
[0019] The sulfide solid electrolyte is selected from Li2GeS3, Li4GeS4, Li2ZnGeS4, Li 4-2x Zn x GeS4 (where 0≤x≤1), Li5GaS4, Li 4+x+y (Ge 1-y-x Ga x )S4 (where 0≤x≤0.2, 0≤y≤1), Li 10 GeP2S 12xy O x F y (where 0≤x≤1, 0≤y≤1), Li 2+2x Zn 1-x GeO4 (where 0≤x≤1), Li 3+z X z Y 1-zO4 (Y=P, As or V; X=Si, Ge or Ti, 0≤z≤1), Li 11-x M 2-x P 1+x S 12 (M=Ge, Sn or Si, 0≤x≤2), xLi2S·(100–x)P2S5 (where x is 50-87.5), Li6PS5X (X=Cl, Br or I), such as Li3PS4, Li7P3S 11 , Li 10 GeP2S 12 、Li6PS5Cl.
[0020] Preferably, the sulfide solid electrolyte is Li6PS5Cl and Li 10 GeP2S 12 According to the compounding of mass ratio 3-5:1, the inventors unexpectedly found that the sulfide solid electrolyte compounded as above can form a better lithium ion transmission network, not only showing a higher lithium ion transmission rate, but also showing better cycle reversibility and higher reversible capacity, which can better promote the conversion of sulfur positive electrode and the use of oxide positive electrode capacity, thereby significantly improving the electrochemical performance of composite positive electrode materials.
[0021] The conductive material is selected from at least one of conductive carbon nanotubes, conductive carbon black (Super P), acetylene black, and Ketjen black.
[0022] The present invention also provides a method for preparing the above-mentioned multi-mechanism energy storage positive electrode material, comprising the following steps:
[0023] (S1) mixing a sulfur-based positive electrode material, an oxide positive electrode material, and a conductive carbon material, ball milling them under an inert atmosphere, and heat treating them to obtain a positive electrode precursor;
[0024] (S2) The cathode precursor and the sulfide solid electrolyte are ball-milled under an inert atmosphere to obtain a multi-mechanism energy storage cathode material.
[0025] Furthermore, if the sulfur-based cathode material is S, step (S1) has a heat treatment step after ball milling. The heat treatment is performed at a temperature higher than 155°C (e.g., 160-200°C) for 5-10 hours. The S element melts above 155°C, and the heat treatment is performed at a temperature higher than the melting point of sulfur. The S element can effectively infiltrate the oxygen-based cathode material and the conductive carbon material, thereby constructing an effective electron transport network.
[0026] The present invention also provides an all-solid-state battery, the positive electrode of which includes the above-mentioned multi-mechanism energy storage positive electrode material.
[0027] Beneficial effects of the present invention:
[0028] 1. By combining the embedded-extracted oxide positive electrode with the converted sulfur-based positive electrode for energy storage, the advantages of the two electrode materials are integrated and the deficiencies of each other are complemented. The oxide positive electrode material after energy storage can replace the conductive carbon material that originally needs to be added to the sulfur-based positive electrode. The conductive carbon material has no electrochemical activity and is an inert component. However, when the inert conductive carbon material is replaced by the oxide positive electrode with high electronic conductivity, not only can the content of the inert component conductive carbon be reduced, but the added oxide positive electrode material can also contribute a certain capacity, which can effectively improve the energy density of the battery.
[0029] 2. Sulfide solid electrolytes can also contribute reversible electrochemical capacity within the charge and discharge range of conversion-type sulfur-based positive electrode materials. In this way, the originally inert electrolyte material has a reduced content of inert components after being replaced with sulfide solid electrolytes. Sulfide solid electrolytes can also contribute capacity as active substances. In this way, the inert components are further reduced and the energy density will be further improved.
[0030] In summary, the multi-mechanism energy storage positive electrode disclosed in the present invention can simultaneously give play to the advantages of oxide-based positive electrode materials and sulfur-based positive electrode materials, and at the same time can utilize the reversible electrochemical capacity of sulfide solid electrolytes, effectively reduce the proportion of inert components such as conductive carbon and electrochemically inactive electrolytes in the positive electrode system, and can greatly improve the energy density of the positive electrode material, which has broad research space and application prospects. BRIEF DESCRIPTION OF THE DRAWINGS
[0031] Figure 1 This is a scanning electron microscope photograph of the multi-mechanism energy storage positive electrode used in Example 1.
[0032] Figure 2 This is a first cycle charge and discharge curve diagram of the all-solid-state battery using the multi-mechanism energy storage positive electrode in Example 1. DETAILED DESCRIPTION
[0033] The present invention is further described below in conjunction with specific examples, but the present invention is not limited to the following examples. The experimental methods described in the following examples are conventional methods unless otherwise specified; the reagents and materials described are commercially available unless otherwise specified. The following specific examples are given to help understand the multi-mechanism energy storage positive electrode described in the present invention.
[0034] Embodiment 1:
[0035] (S1) Composite of sulfur-based positive electrode material and oxide positive electrode material: sulfur element S powder, lithium cobalt oxide LiCoO2 powder, conductive carbon nanotube CNT powder are mixed in a ratio of 80:10:10, and the mixed materials are added to a ball mill protected by argon gas, and the ball-to-material ratio is controlled to 100:1, the rotation speed is 600 rpm, and the ball milling is performed for 8 hours. Then the above mixture is kept at a temperature of 180°C for 6 hours. The sulfur element appears as a flowing liquid above 155°C, which can effectively infiltrate lithium cobalt oxide and conductive carbon nanotubes, and thus an effective electron transport network can be constructed.
[0036] (S2) Composite of composite positive electrode material and sulfide solid electrolyte: The composite positive electrode material obtained in step 1 is mixed with the sulfide solid electrolyte Li6PS5Cl in a ratio of 50:50, and the mixed material is added into an argon-protected ball mill, the ball-to-material ratio is controlled to 100:1, the rotation speed is 600 rpm, and the ball mill is performed for 18 hours to obtain the final multi-mechanism energy storage positive electrode material.
[0037] (S3) Assembling an all-solid-state lithium-sulfur battery: In an argon-protected glove box, pour 80 mg of sulfide solid electrolyte Li6PS5Cl into a mold and apply a pressure of 300 MPa to shape it to obtain a sulfide solid electrolyte Li6PS5Cl ceramic sheet. Pour about 4 mg of the multi-mechanism energy storage positive electrode powder prepared in the above step 2 onto one side of the pressed dual inorganic composite solid electrolyte ceramic sheet, apply a pressure of 500 MPa to make the sulfur positive electrode in close contact with the dual inorganic composite solid electrolyte, and finally place a lithium indium alloy ceramic sheet on the other side of the dual inorganic composite solid electrolyte ceramic sheet, and test the entire battery under a pressure of 100 MPa.
[0038] Figure 1 This is a scanning electron microscope photograph of the multi-mechanism energy storage positive electrode used in Example 1.
[0039] Figure 2 This is a first cycle charge and discharge curve diagram of the all-solid-state battery using the multi-mechanism energy storage positive electrode in Example 1.
[0040] Embodiment 2-8
[0041] The other conditions are basically the same as those in Example 1, except that the types of materials added are different, as shown in Table 1.
[0042] Example 9
[0043] (S1) Composite of sulfur-based positive electrode material and oxide positive electrode material: Li2S powder, lithium cobalt oxide LiCoO2 powder, conductive carbon nanotube CNT powder are mixed in a ratio of 80:10:10, and the mixed materials are added to an argon-protected ball milling tank, with a ball-to-material ratio of 100:1, a rotation speed of 600 rpm, and ball milling for 8 hours to build an effective electron transport network.
[0044] (S2) Composite of composite positive electrode material and sulfide solid electrolyte: The composite positive electrode material obtained in step 1 is mixed with the sulfide solid electrolyte Li6PS5Cl in a ratio of 50:50, and the mixed material is added into an argon-protected ball mill, the ball-to-material ratio is controlled to 100:1, the rotation speed is 600 rpm, and the ball mill is performed for 18 hours to obtain the final multi-mechanism energy storage positive electrode material.
[0045] (S3) Assembling an all-solid-state lithium-sulfur battery: In an argon-protected glove box, pour 80 mg of sulfide solid electrolyte Li6PS5Cl into a mold and apply a pressure of 300 MPa to shape it to obtain a sulfide solid electrolyte Li6PS5Cl ceramic sheet. Pour about 4 mg of the multi-mechanism energy storage positive electrode powder prepared in the above step 2 onto one side of the pressed dual inorganic composite solid electrolyte ceramic sheet, apply a pressure of 500 MPa to make the sulfur positive electrode in close contact with the dual inorganic composite solid electrolyte, and finally place a lithium indium alloy ceramic sheet on the other side of the dual inorganic composite solid electrolyte ceramic sheet, and test the entire battery under a pressure of 100 MPa.
[0046] Examples 10-14
[0047] The other conditions are basically the same as those in Example 9, except that the types of materials added are different, as shown in Table 1.
[0048] Comparative Example 1
[0049] Under high-purity argon conditions, sulfur is used as the positive electrode active material, Super P is used as the conductive additive, and PVDF is used as the binder. The solvent is ethylene carbonate (EC), dimethyl carbonate (DMC), and diethyl carbonate (v / v / v=1:1:1). The electrolyte with the solute being lithium hexafluorophosphate (molar concentration of 1M) is dripped on the positive electrode side, and then the Celgard separator and the original metal lithium negative electrode are added in sequence, and stacked in sequence in the battery shell. The above battery shell is completely sealed and the battery performance test is carried out. The batteries are tested at room temperature, the charge and discharge range is 1.4V-4.3V vs Li (0.8V-3.9V vs lithium indium alloy), and the charge and discharge rate is 0.1C.
[0050] Table 1 Positive electrode electrochemical performance test
[0051]
[0052]
[0053] In summary, the multi-mechanism energy storage positive electrode disclosed in the present invention can simultaneously give play to the advantages of oxide-based positive electrode materials and sulfur-based positive electrode materials, and at the same time can utilize the reversible electrochemical capacity of sulfide solid electrolytes, effectively reduce the proportion of inert components such as conductive carbon and electrochemically inactive electrolytes in the positive electrode system, and can greatly improve the energy density of the positive electrode material, which has broad research space and application prospects.
[0054] According to the comparison between Example 1 and Examples 7 and 8, it can be seen that when the sulfide solid electrolyte is Li6PS5Cl and Li 10 GeP2S 12 When the mass ratio is 3-5:1, the highest capacity and capacity retention rate can be obtained at the same time, indicating that Li6PS5Cl and Li 10 GeP2S 12 There is a certain synergistic effect between them.
[0055] The above content is only a preferred embodiment of the present invention. It should be recognized that this description is not intended to limit the implementation scheme of the present invention. Ordinary technicians in the field can easily make corresponding changes or modifications based on the main concept and spirit of the present invention. Therefore, the scope of protection of the present invention should be based on the scope of protection required by the claims.
Claims
1. A multi-mechanism energy storage positive electrode, characterized in that: The invention comprises the following raw materials in parts by mass: 5-15 parts of oxygen-based positive electrode active material, 35-45 parts of sulfur-based positive electrode active material, 30-50 parts of sulfide solid electrolyte and 3-5 parts of conductive material.
2. The multi-mechanism energy storage positive electrode according to claim 1, characterized in that: The invention comprises the following raw materials in parts by mass: 5 parts of oxygen-based positive electrode active material, 40 parts of sulfur-based positive electrode active material, 50 parts of sulfide solid electrolyte and 5 parts of conductive material.
3. The multi-mechanism energy storage positive electrode according to claim 1, characterized in that: The oxygen-based positive electrode active material includes layered oxide positive electrode materials, spinel-type positive electrode materials and olivine-type positive electrode materials; Preferably, the oxygen-based positive electrode active material includes lithium cobalt oxide (LiCoO2), lithium nickel oxide (LiNiO2), nickel cobalt manganese ternary material (LiNi x Co y Mn 1-x-y O2), lithium nickel cobalt aluminum oxide (LiNi 0.8 Co 0.15 Al 0.05 O2), lithium-rich manganese-based (xLi2MnO3·(1-x)LiMO2), lithium manganese oxide (LiMn2O4), lithium nickel manganese oxide (LiNi 0.5 Mn 1.5 O4), lithium iron phosphate (LiFePO4), lithium manganese phosphate (LiMnPO4), lithium vanadium phosphate (Li3V2(PO4)3), lithium vanadium phosphate (LiVOPO4), lithium cobalt phosphate (LiCoPO4), lithium nickel phosphate (LiNiPO4), lithium iron silicate (Li2FeSiO4), lithium ferrous fluorosulfate (LiFeSO4F), lithium iron borate (LiFeBO3), and lithium iron titanate (Li2FeTiO4).
4. The multi-mechanism energy storage positive electrode according to claim 1, characterized in that: The sulfur-based positive electrode active material is a conversion-type sulfur-based positive electrode material, including sulfur-based materials with electrochemical reversible capacity such as sulfur and metal sulfide; Preferably, the sulfur-based positive electrode active material includes sulfur (S), lithium sulfide (Li2S), iron sulfide (Fe x S y ), titanium disulfide (TiS2), molybdenum disulfide (MoS2), etc.
5. The multi-mechanism energy storage positive electrode according to claim 1, characterized in that: The sulfide solid electrolyte is selected from Li2GeS3, Li4GeS4, Li2ZnGeS4, Li 4-2x Zn x GeS4 (where 0≤x≤1), Li5GaS4, Li 4+x+y (Ge 1-y-x Ga x )S4 (where 0≤x≤0.2, 0≤y≤1), Li 10 GeP2S 12xy O x F y (where 0≤x≤1, 0≤y≤1), Li 2+2x Zn 1-x GeO4 (where 0≤x≤1), Li 3+z X z Y 1-z O4 (Y=P, As or V; X=Si, Ge or Ti, 0≤z≤1), Li 11-x M 2-x P 1+x S 12 (M=Ge, Sn or Si, 0≤x≤2), xLi2S·(100–x)P2S5 (where x is 50-87.5), Li6PS5X (X=Cl, Br or I), such as Li3PS4, Li7P3S 11 , Li 10 GeP2S 12 、Li6PS5Cl.
6. The multi-mechanism energy storage positive electrode according to claim 1, characterized in that: The sulfide solid electrolyte is Li6PS5Cl and Li 10 GeP2S 12 According to the mass ratio of 3-5:
1.
7. The multi-mechanism energy storage positive electrode according to claim 1, characterized in that: The conductive material is selected from at least one of conductive carbon nanotubes, conductive carbon black (Super P), acetylene black, and Ketjen black.
8. The method for preparing the multi-mechanism energy storage positive electrode material according to any one of claims 1 to 7, characterized in that: The following steps are involved: (S1) mixing a sulfur-based positive electrode material, an oxide positive electrode material, and a conductive carbon material, ball milling them under an inert atmosphere, and heat treating them to obtain a positive electrode precursor; (S2) The positive electrode precursor and the sulfide solid electrolyte are ball-milled under an inert atmosphere to obtain a multi-mechanism energy storage positive electrode material.
9. The preparation method according to claim 8, when the sulfur-based positive electrode material is S, step (S1) further comprises a heat treatment step after ball milling, wherein the heat treatment step is performed at a temperature higher than 155°C for 5-10 hours.
10. An all-solid-state battery, characterized in that: The positive electrode of the all-solid-state battery includes the above-mentioned multi-mechanism energy storage positive electrode material.
